Respuesta :

if you notice, it goes form -37, to -35, to -33 and so on.

so is really adding 2 to get the next term,

[tex]\bf -37~~,~~\stackrel{-37+2}{-35}~~,~~\stackrel{-35+2}{-33}~~,~~\stackrel{-33+2}{-31}........[/tex]


so, the common difference is 2, and the first term is of course -37.


[tex]\bf n^{th}\textit{ term of an arithmetic sequence} \\\\ a_n=a_1+(n-1)d\qquad \begin{cases} n=n^{th}\ term\\ a_1=\textit{first term's value}\\ d=\textit{common difference}\\[-0.5em] \hrulefill\\ a_1=-37\\ d=2\\ n=40 \end{cases} \\\\\\ a_{40}=-37+(40-1)2\implies a_{40}=-37+78\implies a_{40}=41[/tex]

ACCESS MORE